1985
DOI: 10.1007/bf01412787
|View full text |Cite
|
Sign up to set email alerts
|

Segmental orientation studies of polyether polyurethane block copolymers with different hard segment lengths and distributions

Abstract: Abstract:The orientation behavior of two series of segmented polyether polyurethanes containing different hard segment length distributions has been studied as a function of the average hard segment length which was varied from one to five methylene bis (p-phenyl isocyanate) (MDI) units. The orientation behavior of the soft segments, isolated hard segments, and of hard segments aggregated in hard domains was determined from the dichroic behavior of representative infrared bands. As the hard segment length incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
70
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 36 publications
10
70
0
Order By: Relevance
“…3). In uniaxial stress, the dichroic ratio increased linearly with ⑀ 1 , as previously seen many times, [14][15][16] showing progressive orientation of the soft-segment chain axis in the stretching direction. In biaxial stress the dichroic ratio did not increase until ⑀ 1 approached 200%; then it increased linearly with a steeper slope.…”
Section: Molecular Orientationsupporting
confidence: 81%
“…3). In uniaxial stress, the dichroic ratio increased linearly with ⑀ 1 , as previously seen many times, [14][15][16] showing progressive orientation of the soft-segment chain axis in the stretching direction. In biaxial stress the dichroic ratio did not increase until ⑀ 1 approached 200%; then it increased linearly with a steeper slope.…”
Section: Molecular Orientationsupporting
confidence: 81%
“…This suggested that only a relatively small fraction of the urethane-containing HS demixed from the polyether SS in these materials. Similar conclusions of incomplete de-mixing can be drawn on the basis of studies using infrared spectroscopy (IR), which indicated some urethane carbonyl groups in non-hydrogen-bonded environments [8,9,11,58]. This interpretation is also consistent with observations of the SAXS invariant by Leung and Koberstein [33], on PEU formulations comparable to those studied here (although those authors attributed their findings to deficits in Dr; due to incomplete de-mixing in both microphases, rather than small values of f for the HSmicrodomains).…”
Section: Resultssupporting
confidence: 54%
“…The strain-softening observed with some TPUs has often been attributed to fragmentation and a decrease in interconnectivity amongst HS microdomains. [8,15,23,33,35] This hypothesis may be well justified for copolymers with a large volume fraction of considerably elongated or interconnected HS microdomains; morphologies such as these have been reported recently by Klinedinst et al [38] for poly(alkylurethane-courea), where the SS and HS compositions are expected to cause stronger and more extensive microphase separation. However, the materials used in the present study are expected to be less strongly microphase-separated, with smaller volume fractions of relatively short HS microdomains.…”
Section: Discussionmentioning
confidence: 81%
“…This was broadly in agreement with previous studies of mechanically deformed TPUs, using SAXS [2,[9][10][11][12]16,17,20,22] and other techniques. [2,3,5,33,[35][36][37] It should be noted that the observed changes in R during uniaxial extension are assumed to be attributable to microdomain rotation. Deformation is thought to be less likely, due to the considerably higher modulus expected for HS microdomains compared with the HS þ SS matrix; this possibility cannot be totally excluded, however, since the expected difference in modulus may be reduced by incomplete segmental demixing.…”
Section: Discussionmentioning
confidence: 99%